Contralateral Upper Limb Weakness Following Botulinum Toxin A Injection for Poststroke Spasticity - Camões-Barbosa, A (2019)
Botulinum toxin type A has been approved for spasticity management in poststroke patients. The adverse effects are generally of two types: those related to local injection; and those related to the systemic effects from spread of the toxin. Contralateral weakness after botulinum toxin A treatment is a rarely reported adverse effect. We report the case of a 33-year-old female who had been receiving regular injections of incobotulinum toxin A due to spasticity of the right limbs after a hemorrhagic stroke. A switch was made to abobotulinum toxin A with an overall conversion ratio of 1:3.83. The patient presented contralateral upper limb paresis, especially of the deltoid muscle, in the second week post-injection. The electroneuromyography showed neuromuscular block due to botulinum toxin A. She recovered completely after eight months. A switch between different formulations of botulinum toxin type A should prompt caution when carrying out unit conversions. Distant side effects may appear, including paresis in the contralateral limbs.